Digitalization in decarbonizing electricity systems – Phenomena, regional aspects, stakeholders, use cases, challenges and policy options. (1st January 2023) - Heymann, Fabian; Milojevic, Tatjana; Covatariu, Andrei; Verma, Piyush
Abstract: Digitalization is a megatrend that affects and transforms societal, economic, and environmental processes on a global scale. Driven by a combination of technological advances as well as shifting societal demands, digitalization also affects the operation and planning of the electricity sector. This paper uses megatrend analysis framework to analyze digitalization phenomena, its regional differences, technologies, use cases and challenges. It highlights potential system-level benefits (e.g., increased efficiency, transparency, consumer participation) and challenges (e.g., electricity demand growth, autonomy loss, increasing cyber risks) currently reported in the literature. Eventually, building on the thorough analysis, we present a menu of policy options to exploit its full potential of digitalized electricity systems while mitigating adverse effects on decarbonization goals and consumers. Highlights: New digital technologies and business models are changing the electricity sector. Consequences and progression of digitalization are not homogeneous between nations. Progress depends on ICT infrastructure, funding, economy, skills, policy/regulation. Policies addressing opportunities and challenges of the transition are needed. Electricity system transformation needs systematic, but contextual approach.